Age and gender related differences of the relationship between anaerobic power production capacity and skating performance in Japanese junior speed skaters - Kumagawa, D.; Tanaka, S.; Tsunoda, N. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
It is well known that the muscle force and power generation capacities are improved by speed skating training (Nemoto et al. 1990, de Koning et al. 1991). And also, these muscle functional characteristics are closely relation to the short-distance skating performance. However, it is not clear whether the effects of age and gender on the strength of relationship between anaerobic power and skating performance. Therefore, this study investigated the age and gender related differences of the relationship between anaerobic power production capacity and skating performance among Japanese male and female speed skaters aged 10-20 years. Methods: Body compositional parameters for body height, body mass, and fat-free mass of the whole body were measured using the body impedance analysis method. Maximal anaerobic power (MAnP) generation capacity was determined using a bicycle ergometer. In addition, the mean 500m skating velocity (SV), calculated from recently attained individual best times, was used as a measure of athletic performance. Furthermore, the subjects (both males and females) were divided into ten groups according to chronological age, and the correlation coefficients between MAnP and SV were examined, respectively. Results: MAnP and SV values increased with chronological age in both males and females. The MAnP of male skaters was significantly higher than that of female skaters after 13 years of age. SV greatly mproved from 11 to 14 years in both male and female skaters, and gender-related differences in SV were observed in all ages except at 11 years. MAnP were significantly correlated with SV in all the age groups. The 12-17-year-old groups among the males and the 10-14-yearold groups among the females showed the high correlation coefficients in terms of the relationships between MAnP and SV. However, significant correlations were not found in any other age groups. Discussion: From these results, it was considered that the growth tendency of anaerobic power and 500m skating velocity were almost the same. However, it was cleared that the contributions of anaerobic power production capacity to speed skating performance may differ with age and gender.